Respuesta :

Answer:5

Step-by-step explanation:

you need to use Pythagoreans theorem

a^2 + b^2 = c^2

said out loud it sounds like

a squared plus be squared equals c squared

The first thing to know is that C is your hypotenuse

That means it is both

  • The longest side of your triangle
  • Side that is across form the 90 degree or right angle

That's the only side that really matters, when you are using the theorem.  The other 2 can be switched and it won't make a difference.

for this problem

a=unknow

b=12

c=13

a^2 + 12^2 = 13^2

a^2 +(12)(12) = (13)(13)

a^2 + 144 = 169

       -144       -144

a^2 = 25

take the square root of both sides

a = 5

ACCESS MORE